Design and prototyping of a development platform for exoskeleton research. - Souza, Rafael Sanchez (2017)
Human machine interface has been a growing field of scientific research for the last years. Conventional robots have been conceived as rigid metallic structures and, when metal meets human tissue, it is necessary to break the mindset in order to achieve better interaction. Exoskeletons, often called wearable robots, shares the same challenges with applications ranging from industry, to military, medicine and entertainment. This work introduces a systematic design of a development platform for exoskeleton research supported by Requirement Engineering and implemented through prototyping. The dynamics of the human joint and the robotic joint are modelled with different couplings between them. A Model Reference Adaptive Control is proposed as a solution for exoskeleton control and simulations indicate that it is capable of estimating human joint parameters in real time. The Model Reference controller is implemented, with successful modulation of the robotic joint apparent impedance. From a practical perspective, we present the design and construction of an experimental workbench and the use of an on-line repository for the control software development. The on-line repository results in a viable way for collaborative project management, software versioning and scientific contribution. The experimental workbench which was designed to meet the stakeholders needs - the university, patients and therapists - being of modular application, easy to operate and relatively low cost, can be used to conduct motor control experiments and rehabilitation tasks.